Water Resources Development Act (WRDA) : Corps of Engineers Project Authorization Issues. (U.S. Congressional Research., 2007)
Reviews provisions of House and Senate versions of the Water Resources Development Act and other Army Corps of Engineers water resources legislation. Discusses Army Corps of Engineers project development reform proposals, issues regarding Corps involvement in environmental infrastructure projects, Upper Mississippi River-Illinois Waterway investments, Everglades restoration implementation, and coastal Louisiana restoration and protection.